2004
DOI: 10.1074/jbc.m408494200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Enzymatically Active Human Cytosolic and Mitochondrial Thioredoxin Reductase in HEK-293 Cells

Abstract: The mammalian thioredoxin reductases (TrxR) are selenoproteins containing a catalytically active selenocysteine residue (Sec) and are important enzymes in cellular redox control. The cotranslational incorporation of Sec, necessary for activity, is governed by a stem-loop structure in the 3-untranslated region of the mRNA and demands adequate selenium availability. The complicated translation machinery required for Sec incorporation is a major obstacle in isolating mammalian cell lines stably overexpressing sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 72 publications
3
47
0
1
Order By: Relevance
“…Recent studies have pointed out that HEK293 cells express several factors that are usually present only in cells of neuronal origin (Shaw et al, 2002;Nalvarte et al, 2004). Therefore, the membrane protrusions formed in HEK293 cells may bear resemblance to polarized neurites (Shaw et al, 2002;Nalvarte et al, 2004;Govek et al, 2005). In this context it is noteworthy that a close homolog of ORP3, ORP6, was identified as one of the fifteen proteins that promote the differentiation of neurons from murine embryonic stem cells (Falk et al, 2007).…”
Section: Journal Of Cell Science 121 (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have pointed out that HEK293 cells express several factors that are usually present only in cells of neuronal origin (Shaw et al, 2002;Nalvarte et al, 2004). Therefore, the membrane protrusions formed in HEK293 cells may bear resemblance to polarized neurites (Shaw et al, 2002;Nalvarte et al, 2004;Govek et al, 2005). In this context it is noteworthy that a close homolog of ORP3, ORP6, was identified as one of the fifteen proteins that promote the differentiation of neurons from murine embryonic stem cells (Falk et al, 2007).…”
Section: Journal Of Cell Science 121 (5)mentioning
confidence: 99%
“…In neuronal cells, serum starvation has been shown to induce integrin-dependent neurite outgrowth, which is highly dependent on Ras-mediated PI3K, Cdc42 and Rac1 activation (Sarner et al, 2000). Recent studies have pointed out that HEK293 cells express several factors that are usually present only in cells of neuronal origin (Shaw et al, 2002;Nalvarte et al, 2004). Therefore, the membrane protrusions formed in HEK293 cells may bear resemblance to polarized neurites (Shaw et al, 2002;Nalvarte et al, 2004;Govek et al, 2005).…”
Section: Journal Of Cell Science 121 (5)mentioning
confidence: 99%
“…[195][196][197] In fact, a study by Mehta et al demonstrated that Sec incorporation efficiency in an in-vitro luciferase reporter system is only approximately 5-8% the levels of the wild-type luciferase. 198 …”
Section: Expression Of Selenoproteins In Plasmamentioning
confidence: 99%
“…These enzymes are key components of the thioredoxin system, which is one of major redox systems in cells. They control the redox state of thioredoxin but were also implicated more broadly in redox regulation, cell growth, and other functions (4,5). Two TRs, TR1 (also known as TrxR1 and Txnrd1) and TR3 (also known as TrxR2 and Txnrd2), have been characterized in detail and are components of cytosolic and mitochondrial thioredoxin systems, respectively.…”
Section: Thioredoxin Reductases (Tr(s))mentioning
confidence: 99%